The role of User Generated Content (UGC) platforms in shaping behavioral purchase intention in Bangladesh - Datta, Anubhav (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.